Breaking constraint: axial patterning in Trichechus (Mammalia: Sirenia). Issue 6 (22nd October 2014) - Buchholtz, Emily A.; Wayrynen, Kaisa L.; Lin, Iris W.
SUMMARY Meristic variation is often limited in serially homologous systems with high internal differentiation and high developmental modularity. The mammalian neck, an extreme example, has a fixed (at seven) count of diversely specialized segments. Imposition of the mammalian cervical constraint has been tentatively linked to the origin of the diaphragm, which is muscularized by cells that migrate from cervical somites during development. With six cervical vertebrae, the genus Trichechus (manatee) has apparently broken this constraint, although the mechanism of constraint escape is unknown. Hypotheses for the developmental origin of Trichechus cervical morphology include cervical rib 7 repatterning, a primaxial/abaxial patterning shift, and local homeosis at the cervical/thoracic boundary. We tested predictions of these hypotheses by documenting vertebral morphology, axial ossification patterns, regionalization of the postcranial skeleton, and the relationship of thoracic ribs to sternal subunits in a large data set of fetal and adult Trichechus and Dugong specimens. These observations forced rejection of all three hypotheses. We propose alternatively that a global slowing of the rate of somitogenesis reduced somite count and disrupted alignment of Hox‐generated anatomical markers relative to somite (and vertebral) boundaries throughout the Trichechus column. This hypothesis is consistent with observations of the full range of traditional cervical morphologies in the six cervical vertebrae, conserved postcranial proportions, and column‐wide reduction in count relative to its sister taxon, Dugong. It also suggests that the origin of the mammalian cervical constraint lies in patterning, not in count, and that Trichechus and the tree sloths have broken the constraint using different developmental mechanisms.